A new species of Derobrachus Audinet-Serville, 1832 (Coleoptera, Cerambycidae, Prioninae) from a cloud forest in Honduras - Santos-Silva, Antonio; Mal, Noël; Roie, Martijn Van; Jocqué, Merlijn (Zootaxa, 2018)
A yearly biodiversity monitoring of longhorned beetles (Cerambycidae) in a Honduran cloud forest revealed a new species of prionine. Derobrachus cusucoensis sp. nov. is a locally relatively common species described from Cusuco National Park in Honduras, becoming the ninth species of this genus recorded for the country. Similar both in morphology and a montane habitat to D. dohrni, there is a possibility that this new species represents a disconnected population from the latter that evolved separately. An adapted insert for an existing identification key to all Derobrachus species is included.